2022
DOI: 10.1186/s12989-022-00490-x
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide and carbon black nanoparticles disrupt neuronal homeostasis via excessive activation of cellular prion protein signaling

Abstract: Background Epidemiological emerging evidence shows that human exposure to some nanosized materials present in the environment would contribute to the onset and/or progression of Alzheimer’s disease (AD). The cellular and molecular mechanisms whereby nanoparticles would exert some adverse effects towards neurons and take part in AD pathology are nevertheless unknown. Results Here, we provide the prime evidence that titanium dioxide (TiO2) and carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The increased production of ROS after administration of TiO 2 -NPs may be rationalized by activation of heme oxygenase 1 through p38-Nrf-2 signaling pathway or attachment of TiO 2 -NPs to prion protein the plasma membrane protein which distorts prion signaling function. This prompts the activation of NADPH oxidase via prion-dependent pathway and consequently increases the production of ROS that changes redox equilibrium 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The increased production of ROS after administration of TiO 2 -NPs may be rationalized by activation of heme oxygenase 1 through p38-Nrf-2 signaling pathway or attachment of TiO 2 -NPs to prion protein the plasma membrane protein which distorts prion signaling function. This prompts the activation of NADPH oxidase via prion-dependent pathway and consequently increases the production of ROS that changes redox equilibrium 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…178 Furthermore, exposure to TiO 2 NPs was associated with varying degrees of cytotoxicity to the human cerebral endothelial cell line (HCECs), human neural stem cell line (hNSCs), and neuroectodermal stem cell line (1C11) models. [179][180][181] See Table 7 for details. The neurotoxic effects of TiO 2 NPs are influenced by various factors.…”
Section: Neurotoxic Effects Of Tio 2 Nps In Vitro Modelsmentioning
confidence: 99%
“…In addition to aggregation of α-synuclein and tau protein, TiO 2 NPs were also shown to have a significant effect on β-amyloid production. Ribeiro et al (2022) [124] demonstrated that direct interaction of TiO 2 NPs with neuronal membrane prion protein (PrP C ) results in activation of NADPH-oxidase and 3-phosphoinositide-dependent kinase 1 (PDK1) with subsequent internalization of TACE αsecretase, resulting in increased sensitivity to TNFα and accumulation of amyloid precursor protein with amyloid Aβ40/42 overproduction. In addition, genotoxic effects of oral TiO 2 NP exposure evidenced by DNA fragmentation were also associated with a point mutation at exon 5 of PSEN1 gene that is known to be associated with inherited forms of Alzheimer's disease [125].…”
Section: Protein Aggregation and Neurodegenerationmentioning
confidence: 99%